Procalcitonin as a marker of neonatal sepsis - Nazeer Ahmad Jeergal; Rizwan-; Naushad Ali .N. Malagi; Faisal Farooqui; Sadashiva .B. Ukkali; Ravindra Naganoor; A.N. Thobbi (Al Ameen Medical College, 2016)
Introduction: Neonatal sepsis is one of the commonest causes of neonatal mortality in the developing world. Procalcitonin (PCT) has emerged as the most studied and promising sepsis biomarker. Objective: To assess the role of procalcitonin (PCT) as a marker in the early diagnosis, treatment and follow-up of neonatal sepsis. Methods: Twenty five neonates with clinical (n=5), suspected (n=13) and proven sepsis (n=7) were evaluated. The PCT levels were measured by immunoluminoassay before and on day 5 of treatment. PTC levels of 0.5-2 ng/ml, 2.1-10 ng/ml and >10 ng/ml were considered as weakly positive, positive and strongly positive, respectively. Findings: The levels of PCT in proven sepsis group were higher than that in other groups. Strongly positive PCT level was seen in 2 cases of proven sepsis, 5 cases of suspected sepsis and in 1 case of clinical sepsis. PCT levels were dramatically decreased in three groups on day 5 of treatment. Conclusion: The results show that the serum procalcitonin levels seem to be significantly increased in proven sepsis and decrease dramatically in all types of sepsis after appropriate treatment.